Hydrolytic stability in hemilabile metal–organic frameworks. Issue 11 (November 2018) - McHugh, Lauren; McPherson, Matthew; McCormick, Laura; Morris, Samuel; Wheatley, Paul; Teat, Simon; McKay, David; Dawson, Daniel; Sansome, Charlotte; Ashbrook, Sharon; Stone, Corinne; Smith, Martin; et al.
Abstract Highly porous metal–organic frameworks (MOFs), which have undergone exciting developments over the past few decades, show promise for a wide range of applications. However, many studies indicate that they suffer from significant stability issues, especially with respect to their interactions with water, which severely limits their practical potential. Here we demonstrate how the presence of 'sacrificial' bonds in the coordination environment of its metal centres (referred to as hemilability) endows a dehydrated copper-based MOF with good hydrolytic stability. On exposure to water, in contrast to the indiscriminate breaking of coordination bonds that typically results in structure degradation, it is non-structural weak interactions between the MOF's copper paddlewheel clusters that are broken and the framework recovers its as-synthesized, hydrated structure. This MOF retained its structural integrity even after contact with water for one year, whereas HKUST-1, a compositionally similar material that lacks these sacrificial bonds, loses its crystallinity in less than a day under the same conditions. The promise shown by metal–organic frameworks for various applications is somewhat dampened by their instability towards water. Now, an activated MOF has shown good hydrolytic stability owing to the presence of weak, sacrificial coordination bonds that act as a 'crumple zone'. On hydration, these weak bonds are cleaved preferentially to stronger coordination bonds that hold the MOF together.